Endoscopic imaging results: web based solution with video diffusion - Braga, Joel Teles (2013)
In this paper we present a solution for diffusion of endoscopic imaging results. The aim is to solve the problem of endoscopy examinations access anywhere within a health care network by authorized health care professionals and researchers avoiding the need to repeat unpleasant exam procedures. The presented solution also enables streaming in real time of exams being carried out, which means that the health professionals can contribute with their expertise even when, for some reason, they cannot attend the exam onsite. All this information is archived and accessible at any moment. The proposed solution also provides tools to export the exams in any video format.